Renal angina index in pediatric septic patients as a predictor of acute kidney injuryin remote area - Nugroho Setia Budi, -
Abstract Background: One of the most common sepsis comorbidities is severe acute kidney injury (AKI), which occurs in about 20% of pediatric patients with severe sepsis and is independently associated with poor outcomes. Many studies have shown the ability of renal angina index (RAI) with a cut-off point of 8 to predict the risk of AKI grade 2 and 3, but with varying sensitivity and specificity. Therefore, this study aims to identify a RAI cut-off point to predict the incidence of AKI in pediatric septic patients in the setting of a regional hospital in Indonesia. Methods: An observational analytic study with a prospective longitudinal design was conduct-ed on 30 pediatric patients in the Resuscitation Room of Dr. Soetomo General Hospital Sura-baya. Patients who met the inclusion criteria were given 1-hour standardized resuscitation, then were observed. Every action taken to the patient was recorded, fluid input and output were measured, and mechanical ventilation and vasopressor administration were documented until the third day to determine factors influ-encing the incidence of AKI. Results: In this study, 56.7% of pediatric septic patients had AKI. The Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score in this study had a median of 11, in accordance with the pediatric sepsis guideline. RAI, with a cut-off point of 8 as a predictor for AKI grade 2-3, had a sensitivity of 100% and a specificity of 68% (area under the curve [AUC]=0.912). In terms of AKI risk tranche, the majority of patients (93.1%) had mechanical ventilation, while in terms of AKI injury tranche, the majority met the fluid overload criteria (79.3%). Conclusion: RAI, with a cut-off point of 8, can be used as a predictor for severe AKI in pediatric septic patients.